Pendampingan Pembuatan Buku Ajar Imla’ Sekolah Dasar Islam Terpadu (SDIT) Ponpes Baitussalam, Simpang Mangga, Simalungun - Manshuruddin Manshuruddin; Sopian Lubis; Ryandi Ryandi (Universitas Islam Negeri Sumatera Utara, 2021)
ABSTRACT. The goal of this community service is to produce Imla textbok forintegrated Islamic elementary school, Pesantren Baitussalam, Simalungun. There are six teachers of Imla’ mentored in this program. The program was held at pesantren Baitussalam for 3 days. To achieve the goal, we conducted a workshop (intensive dialogue and direct practice). After doing this, we found that first, the teacher’s ability is very qualified to teach the subject i.e imla. It is because most of them were graduated from pesantren, second, the teachers have succeeded in producing syllabus and textbooks of Imla from grade 1 to 6— which is structured according to the level of students. It is hoped further activities that the syllabus and textbooks are taught by IT-based learning model. Keywords: Imla’, textbook, pesantren